2015
DOI: 10.1097/shk.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Mediated Gut Protection After Hemorrhagic Shock is Lessened in Syndecan-1−/− MICE

Abstract: We have shown in a rodent model of hemorrhagic shock (HS) that fresh frozen plasma (FFP) reduces lung inflammation and injury which are correlated with restitution of syndecan-1. Since the gut is believed to contribute to distant organ injury and inflammation after shock, the current study sought to determine if the protective effects of plasma would extend to the gut and to elucidate the contribution of syndecan-1 to this protective effect. We also examined the potential role of TNFα, and a disintegrin and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Plasma is an effective buffer of fibrinolytic activity (19) and effectively reverses hyperfibrinolysis and reduces mortality in hyperfibrinolytic rodents (20). This effective colloid also has been shown to enhance metabolic recovery (21) from hemorrhagic shock, restore the endothelial glycoalyx (22), reduce pulmonary injury (23) and reduce gastrointestinal damage (24). Additional blood products that impact fibrinolysis include cryoprecipitate, which has been found to have a similar survival advantage as TXA (25).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is an effective buffer of fibrinolytic activity (19) and effectively reverses hyperfibrinolysis and reduces mortality in hyperfibrinolytic rodents (20). This effective colloid also has been shown to enhance metabolic recovery (21) from hemorrhagic shock, restore the endothelial glycoalyx (22), reduce pulmonary injury (23) and reduce gastrointestinal damage (24). Additional blood products that impact fibrinolysis include cryoprecipitate, which has been found to have a similar survival advantage as TXA (25).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that syndecan-1 is shed after hemorrhagic shock from both the lung and gut (14,15). Shedding of the cell surface ectodomain of syndecan-1 is regulated by multiple intracellular signaling pathways converging on a diverse group of proteases, referred to as sheddases.…”
Section: Introductionmentioning
confidence: 92%
“…Laboratory data suggest that plasma has benefits beyond the coagulation system, including restoration of endothelial glycocalyx 11 and reduction of intestinal permeability, 12 metabolic derangements, 13 and hyper-fibrinolysis. 14 Prehospital plasma infusion has been shown to be feasible during helicopter transport, 15 but the logistics of storage and thawing in fast ground transport have been challenging.…”
Section: Introductionmentioning
confidence: 99%